Entrepreneurial orientation as a catalyst for innovation in enhancing the performance of SME in F&B sector - Yusuf, Yusni Munirah; Ab Rahman, Ab Rahman; Bustaman, Hasnun Anip (Journal of Islamic, Social, Economics and Development, 2025)
This paper represents a conceptual framework that explores the relationship between entrepreneurial orientation on business performance of food and beverages small and medium enterprise (SME) in Malaysia. In adversely changing market of F&B, there is a need for an entrepreneur to have EO to foster innovation so that the business can sustain. This study examines the relationship between entrepreneurial orientation and product innovation and entrepreneurial orientation and business model innovation impact on business performance, thus, serves as framework foundation for both academic research and practical implication for the future researcher.